A novel method for measuring the extragalactic background light: Fermi application to the lobes of Fornax A - Georganopoulos, M; Sambruna, R; Kazanas, D; Cillis, A; Cheung, C; Perlman, E; Blundell, K; Davis, D (Institute of Physics Publishing, 2008)
We describe a new method for measuring the extragalactic background light (EBL) through the detection of $γ$-ray inverse Compton (IC) emission due to scattering of the EBL photons off relativistic electrons in the lobes of radio galaxies. Our method has no free physical parameters and is a powerful tool when the lobes are characterized by a high energy sharp break or cutoff in their electron energy distribution (EED). We show that such a feature will produce a high energy IC `imprint' of the EBL spectrum in which the radio lobes are embedded, and show how this imprint can be used to derive the EBL. We apply our method to the bright nearby radio galaxy Fornax A, for which we demonstrate, using WMAP and EGRET observations, that the EED of its lobes is characterized by a conveniently located cutoff, bringing the IC EBL emission into the {\sl Fermi} energy range. We show that {\sl Fermi} will set upper limits to the optical EBL and measure the more elusive infrared EBL.